Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.5122
|View full text |Cite
|
Sign up to set email alerts
|

SAT0682 Prevalence of sarcopenia in patients with chronic inflammatory rheumatic diseases

Abstract: BackgroundEvaluation of sarcopenia is of major relevance because of these clinical repercussions on morbidity and mortality. Although the definition should include both low muscle mass and function, a combination of the 2 criteria was not reported in inflammatory rheumatic diseases (IRDs).ObjectivesTo determine in a cohort of IRDs the prevalence of sarcopenia using established combined criteria (EWGSOP) (1).MethodsSarcopenia defined as both low muscle mass (skeletal muscle index (SMI) <7.26 kg/m2 for men; <5.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Demographics are shown in Table 3. Studies did not differentiate outcomes according to subtypes of psoriatic disease; however, five of the studies focused purely on psoriatic arthritis [18][19][20][21][22]. Only four studies [21][22][23][24] reported on the racial and ethnic groups of participants.…”
Section: Population Sampledmentioning
confidence: 99%
See 4 more Smart Citations
“…Demographics are shown in Table 3. Studies did not differentiate outcomes according to subtypes of psoriatic disease; however, five of the studies focused purely on psoriatic arthritis [18][19][20][21][22]. Only four studies [21][22][23][24] reported on the racial and ethnic groups of participants.…”
Section: Population Sampledmentioning
confidence: 99%
“…Only four studies [21][22][23][24] reported on the racial and ethnic groups of participants. A control group was assessed in 10 studies [18,20,21,23,[25][26][27][28][29][30], and this information was missing in another study [19]. None of the studies reported on socio-economic status, including employment or educational attainment of subjects.…”
Section: Population Sampledmentioning
confidence: 99%
See 3 more Smart Citations